Documentation on ecclesiastic of Navarre institutions in Section of Clergy of the Historical National Archive - de la Cruz Herranz, Luis Miguel (Huarte de San Juan. Geografía e Historia, 2010)
The content from Navarra of the Clergy Section of the National Historical Archive, as well as those of Sigillography and Codes, which were deposited, originating partly from the Confiscation. The material from the monasteries of San Salvador de Leire and Santa María de Fitero stand out due to the volume of their content. In order to have an overall view of the whole, those preserved in the Archive of the Kingdom of Navarre are also indicated.